Globalisation, Working Conditions, Cheap Labour and Employment Relations in Kenya - Olungo, Kennedy; Ukpere, Wilfred (Journal of Reviews on Global Economics, 2018)
People perceive globalisation differently. Some consider it to be the internationalisation of local economies in terms of trade, foreign direct investments, agriculture, technology transfer and dominant culture, amongst others. However, globalisation, with its liberalisation and deregulation policies, seem to have created additional turmoil in the workplace as far as employment relations is concerned. The main objective of this paper was to investigate how globalisation has influenced employment regulations/deregulations in Kenya. The study adopted an explanatory mixed method approach. About 500 closed ended questionnaires were distributed to employees of the sampled companies, and of these, 483 were satisfactorily completed, which culminated in a 97% response rate. In addition, 10 key employment relations stakeholders were interviewed for the qualitative phase of the research study. The study revealed that the conditions of workers, in terms of health, have improved in Kenya since globalisation. It also reflected that working conditions, particularly regarding safety, have improved since globalisation. The study further showed that organisations in Kenya are exploiting children, who are part of their unskilled workforce, by paying them low wages, which reflects a recent, rising trend in the use of child labour in Kenya, particularly in manufacturing sectors. Thus, the study’s findings show that there has been an increase in the use of cheap labour amongst Kenyan organisations. In addition, the study indicates that Kenyan companies favour foreign employees compared to local ones in terms of salaries and wages.